Stephen Hawking's Atheist View on Science ; A Critics from Philosophy of Islamic Education - Syamsuar Hamka Hamka; Aswar Aswar; Askar Fatahuddin (Universitas Darussalam Gontor, 2023)
Religions, for most western scientists, do not develop linearly with science. Because since the beginning, religion has been removed from the world of scientific research. Efforts to approach nature are freed from metaphysical elements, which according to al-Attas, Nature is no longer considered sacred. As a result, it is permissible to act freely against nature. Nature is only limited to the framework of mechanistic philosophy which furthermore becomes the philosophical foundation for the development of modern science. This study examines the implications of Stephen Hawking's Atheist View on Science for the modern education in Indonesia according to The Philosophy of Islamic Education. This research begins with data reduction, data presentation, and drawing conclusions based on a combination of information about the object of research after analyzing Hawking's atheist view on science and its implications for the modern education in Indonesia according to The Philosophy of Islamic Education. This research shows that, according to Hawking, the only instrument that can explain the nature of the universe is science. And in the creation of the universe, there was no need for an entity called God. Consequently, Stephen Hawking's atheist view towards science has profound implications for 1) the purpose of education. With the concept of nature based on atheism, the purpose of education will also potentially remove the element of God from the equation. 2) the curriculum. An education system built on reduced epistemological concepts will end up with the marginalization of metaphysics. 3) the educational approaches. Approaches to science that are based on atheism do not touch the moral-religious aspects. 4) evaluation system. An evaluation system that is based on atheism will also result in an assessment that emphasizes more on cognitive aspects and tends to ignore aspects of morals and manners.